Pemberian Asi Eksklusif dan Usia Pemberian Makanan Pendamping Asi dengan Status Gizi Bayi Usia 6-12 Bulan - Aida Fitriani; Hafsah Us; Nizan Mauyah (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the relationship between the exclusive breastfeeding age at which MP-ASI is given and infants' nutritional status (6-12 months) at the Syamtalira Aron Health Center, North Aceh District. The research method used was case control by comparing 50 malnourished and 50 well-nourished infants. The results showed a significant relationship between exclusive breastfeeding (p=0.005), the age at which complementary feeding was given (p=0.002), and nutritional status. The most dominant factor was exclusive breastfeeding with the nutritional status of infants aged 6-12 months (p=0.003), OR: 4.497 (95% CI: 1.661 – 12.177). In conclusion, some babies are not given exclusive breastfeeding and complementary foods that are not age-appropriate for babies aged 6-12 months. This type of combined MP-ASI has a higher average weight gain when compared to babies who receive local and manufactured complementary foods. Keywords: Exclusive Breastfeeding, Infants, Complementary Foods for Breastfeeding, Nutritional Status